2017
DOI: 10.1097/tp.0000000000001752
|View full text |Cite
|
Sign up to set email alerts
|

Wait Time of Less Than 6 and Greater Than 18 Months Predicts Hepatocellular Carcinoma Recurrence After Liver Transplantation

Abstract: Background It has been postulated that short wait time before liver transplant (LT) for hepatocellular carcinoma (HCC) results in the inclusion of tumors with aggressive biology, but prolonged wait time could result in a shift to more aggressive tumor behavior. We therefore test the hypothesis that a wait time “sweet spot” exists with a lower risk for HCC recurrence compared to the other 2 extremes. Methods This multi-center study included 911 patients from 3 LT centers with short, medium and long wait times… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
68
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 71 publications
(74 citation statements)
references
References 41 publications
4
68
0
Order By: Relevance
“…In a large analysis of >5,000 HCC patients in the UNOS region those who remained on the waiting list without recurrence for >120 days had a 40% reduced risk of post-LT recurrence compared to those with a shorter waiting time (28). This "sweet spot" of 6-18 months waiting time has also been demonstrated by a very recent study (29). Another analysis of UNOS data showed that a higher MELD score at LT was independently associated with lower post-LT mortality in HCC patients but with a higher mortality in non-HCC patients (30).…”
Section: Futility Rule #1: Extrahepatic Metastases and Macrovascular mentioning
confidence: 67%
“…In a large analysis of >5,000 HCC patients in the UNOS region those who remained on the waiting list without recurrence for >120 days had a 40% reduced risk of post-LT recurrence compared to those with a shorter waiting time (28). This "sweet spot" of 6-18 months waiting time has also been demonstrated by a very recent study (29). Another analysis of UNOS data showed that a higher MELD score at LT was independently associated with lower post-LT mortality in HCC patients but with a higher mortality in non-HCC patients (30).…”
Section: Futility Rule #1: Extrahepatic Metastases and Macrovascular mentioning
confidence: 67%
“…The three components of the RETREAT score are AFP at LT, microvascular invasion, and the sum of the largest viable tumor plus number of viable tumors on explant. The methods used to create the RETREAT score have been described . Explant pathology was also reviewed to determine histologic grade based on the modified Edmondson criteria …”
Section: Methodsmentioning
confidence: 99%
“…Because Region 5 has one of the longest wait times to LT in the United States, and very short wait time has been linked with worse post‐LT outcomes in HCC, the results from Region 5 may not be generalizable across other regions. Additionally, little is known about the post‐LT outcomes after down‐staging in patients with initial tumor burden exceeding UNOS‐DS criteria.…”
mentioning
confidence: 99%
“…pertaining to the fact that other potentially curative tumor-directed therapies are available to many patients F I G U R E 2 Cumulative incidence of waitlist dropout due to tumor progression, being too sick to undergo livertransplant, or death by listing characteristics. This approach has remained unchanged for >15 years, despite ample evidence that the risk of dropout varies not only by wait time region4,19,27 but also by tumorrelated features (eg, tumor burden, AFP, response to LRT) B, Child-Pugh class.…”
mentioning
confidence: 99%